Collections held by the Mollusca Section of the British Museum (Natural History) relating to Australia, New Zealand and the Pacific (as filmed by the AJCP) [M2500] - Australian Joint Copying Project; National Library of Australia; State Library of New South Wales; British Museum (Natural History) (Canberra : Australian Joint Copying Project, 1950)
1. Letter from D.D. Baldwin re Sandwich Island shells. 2. Papers re British, Australian, New Zealand, Antarctic Research Expedition (BANZARE), 1938-9, 1951. 3. "A provisional catalogue of worldwide recent species of the family naticidae (Mollusca Gastrapoda)", 1977 / R.M. Dixon. 4. Catalogue of shell collection, 1869-1929 . 5. J. Longstaff notebook for collecting trip in Australia and N.Z., 1909-10. 6. Alfred J. Peile correspondence, 1922-29 re Lord Howe Island and Norfolk Island shells. 7. A. Powell papers, 1937. 8. William James Rees, file on Archatina (giant African snail). 9. Papers from Museum staff on mollusca specimens from the Terra Nova expedition, 1914-29.
Filmed as part of the Australian Joint Copying Project by the National Library of Australia and the State Library of New South Wales.
National Library of Australia holds microfilm master.
Australian Joint Copying Project miscellaneous series M2500.
Also available online
Microfilm copy of originals held by British Museum (Natural History), London.
Descriptive list available (2 p.)
Keywords: Shells; Mollusks; Naticidae; Achatina